The Influence of Finger Puppet Media on Students' High Level of Thinking Ability in Elementary School - Risma Nuriyanti; Abih Gumelar (Universitas Sebelas Maret, 2021)
The low level of thinking ability of elementary school students is one of the problems that need to be considered. This study aims to know the influence of finger puppet media on students' high level of thinking ability in elementary school. The method used is a quarquis of nonequivalent control group design experiments. The population in this study was fourth grader in one of bandung elementary school which numbered 47 students and divided into two classes, namely experimental class and control class. The results showed there was a significant difference between posttest experiment class and control class. From these results it can be concluded that finger puppet media has a significant influence on students' high level of thinking ability in elementary school. Thus, students get meaningful learning and teachers get learning media that is able to improve students' high level of thinking ability which is assessed from the ability to analyze, which includes 3 indicators, namely determining the theme, determining the main idea, and determining the content of the story message.